(3ahGFO YhGFO aj eSCdI GdVOs - (3eMeO GdMSjfj GdajQhR BHGOjs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3bO fXeJgG aj Sdc GdJMQjQ dJchf JPcQI hJHUQI hYdi GdfGXQ QYGjI MSf GdSdjaI hGdHjYI GdeSJbjeI , ebOeI aj HjGf GLeGdj CeQjf GdChd Cf GdGTcGd aj YbO GdHMK ddVO ef MjK chf GdHMK Yf GdebOeI eZfjG Yfg (B...s
(3BNQgG (B:s
... (3cGf jbhd dG JXde GdHjJ Cj dG JHbjY Ydi GdXdeI ajSJaGO efg YQaG CeQ HGdVO Cj VqhFg HVhFg hef gfG GTJHg HYV abGd Gf bhd GdMQGf Yjf aYd GdVO ceG CTQfG SGHbG gPG BNQ eG GhQOfGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3CUhd Gdabgs